Pharmaceutical Telemonitoring for Patients with Psychiatric Disorders: Implementation Description - Camila Lima; Joslene Barreto; Max Viana; Izabel Alves (University of Minnesota Libraries Publishing, 2024)
Telecare has exhibited efficacy in managing various chronic clinical conditions and presents potential in the surveillance of patients with psychiatric disorders, an area necessitating further investigation. Herein, we delineate an adjunct for pharmacotherapeutic oversight of individuals with psychiatric disorders receiving care at a public mental health outpatient facility. This manuscript serves as an implementation dossier detailing the progression of a preliminary trial. The non-probabilistic sample consisted of 21 patients, monitored between January 2022 and October 2022. Predominantly, schizophrenia constituted the primary psychiatric disorder among the cohort, accounting for 61.9% of cases. Across 79 remote consultations, averaging 3.8 consultations per patient, text messages constituted 52% (41/79) of the interactions. Throughout the telemonitoring process, diligent monitoring of patients' self-reported concerns was facilitated, permitting pharmaceutical interventions encompassing health advisories (52.7%) and recommendations for therapeutic adjustments (34.4%). Consequently, telemonitoring yielded an augmented pharmaceutical support framework for psychiatric patients, thereby presenting a plausible avenue for enhancing accessibility within public healthcare institutions.